2016
DOI: 10.1038/srep24517
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell Count Correlates with Colorectal Neoplasm Progression and Is a Prognostic Marker for Distant Metastasis in Non-Metastatic Patients

Abstract: Enumeration of circulating tumor cells (CTCs) has been proven as a prognostic marker for metastatic colorectal cancer (m-CRC) patients. However, the currently available techniques for capturing and enumerating CTCs lack of required sensitivity to be applicable as a prognostic marker for non-metastatic patients as CTCs are even more rare. We have developed a microfluidic device utilizing antibody-conjugated non-fouling coating to eliminate nonspecific binding and to promote the multivalent binding of target cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 21 publications
8
107
1
1
Order By: Relevance
“…It was found that CTCs were associated with tumor de-differentiation, lymphatic invasion, TNM stage, and serum CEA level, which were consistent with the results of previous studies [30, 31]. In addition, serum CEA values in CTCs-positive patients were higher than CTCs-negative patients, which indicated that patients with high CEA levels had more opportunities to be CTCs-positive.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that CTCs were associated with tumor de-differentiation, lymphatic invasion, TNM stage, and serum CEA level, which were consistent with the results of previous studies [30, 31]. In addition, serum CEA values in CTCs-positive patients were higher than CTCs-negative patients, which indicated that patients with high CEA levels had more opportunities to be CTCs-positive.…”
Section: Discussionsupporting
confidence: 89%
“…Our result has revealed that CTC positive rates were associated with indicators of poor prognosis. Therefore, CTCs may be an important prognostic indicator in CRC which has been validated by other research that its presence associated with shorter DFS and OS [30–32]. A recent study showed that both CTC detection rates and CTC counts had significant correlation with tumor progression and the appearance of distant metastases in non-metastatic CRC patients [32].…”
Section: Discussionmentioning
confidence: 93%
“…CellMaxLife is currently conducting clinical trials on using an automated liquid biopsy platform CellMax CTC (CMx) [85,121] for early detection of colorectal (NCT03476122), prostate (NCT03488706), and breast cancer (NCT03511859).…”
Section: Translational Statusmentioning
confidence: 99%